The effectt of natural fiber using lalang grass as an additive in reinforced concrete on compressive strength and flexural strength - Ridawanah, Upe (2013)
Concrete is the main material in construction industry. Concrete is the combination of Ordinary Portland Cement, fine and coarse aggregate, and water. The water and Ordinary Portland Cement will react by hydration process which will form cement paste. This cement paste will make the combination in making concrete become more solid and hard material. The concrete is low in compression but high in tensile strength. Nowadays, the researchers found new technology to improve the strength of concrete by using natural fiber as an additive or replacement material in the reinforced concrete. There are many types of natural fiber used in reinforced concrete, such as Leaf fiber, Grass fiber and reeds fiber. The natural fiber is used because of low cost and low impact to environment.In this study, the Lalang Grass was used as an additive in the reinforced concrete. Lalang Grass is a natural fiber that in the categories of Grass fiber. Lalang Grass is a plant that does not shows any economical value, and also gives problem to control its breeding. The Lalang Grasses are used for different percentage of Lalang Grass such as 0.1%, 0.2% and 0.3% by weight of cube and beam specimen. The cube and beam specimen are cured for different age of curing. For cube specimens are cured for 7, 14 and 35 days, while the beam specimens are cured for 35 days. The compression and flexural test were the testing for cube and beam specimen respectively. The compression and flexural test are conducted at the end of age of curing and the result of average for cube and beam specimens of the testing were the ideal result for the compressive strength and flexural strength. The result of compression test shows that an addition of Lalang Grass can improve the strength of compressive strength.This is because when the period of age of curing become longer, the compressive strength also increase. The 0.3% of Lalang Grass as an additive had the higher compressive strength compare with the other percentage of Lalang Grass. For the flexural strength, the 0.3% of Lalang Grasses an additive shows the potential to improve the flexural strength of the concrete. this is because, the flexural strength of Ordinary Portland Cement concrete with 0.3% of Lalang Grass had higher strength compare plain Ordinary Portland Cement concrete and Ordinary Portland Cement concrete with 0.2% of Lalang Grass.